Influence of the physical morphological characteristics of mineral fillers on the bitumen-filler interfacial interaction. (16th May 2023) - Sun, Huadong; Pang, Laixue; Ding, Yongling; Xing, Baodong; Tang, Yijun; Sun, Xin; Yuan, Jiacheng; Zhou, Liang; Wang, Yafei; Lyu, Yuchao; Sha, Fei
Graphical abstract: Highlights: The morphological indicators of limestone filler greatly affect the asphalt-filler interaction. The morphology pattern of fillers were observed with improved carrier slide technology. The smallest filler size range of F4 with larger SSA exhibited the best lipophilic performance. The interaction parameter C could better distinguish the interaction ability of bitumen-filler. FF and SSA as primary factors affecting the bitumen-filler interaction were studied. Abstract: In this paper, the physical and morphological indexes of limestone mineral filler and their influence on the interfacial performances between asphalt and filler were investigated. The characterization methods of structural and physical pattern tests of the filler particles were improved and carried out using carrier slide technology incorporating digital image technology. The role of filler particles in terms of density, porosity, aspect ratio, angularity indices, fractal dimension and feature roughness as a function of their physical features presented a decrease trend with the smaller particle sizes, while the specific surface area and shape factor displayed an opposite trend. The effect of limestone filler morphology on asphalt-filler interaction were analyzed and observed based on the viscoelastic parameters and relevant theoretical models. The dynamic shear rheometer measurement was performed to examine the three interaction parameters A, B, and C. The interaction forces were positive and negative correlation with the experimental temperature and the particle size of limestone filler, respectively. The sensitivity analysis demonstrated that, regardless of the test temperature and particle size fraction, the sensitivity priority of interaction parameter was in the sequence of C > A > B. Furthermore, grey correlation analysis was performed to investigate the influence of the morphology patterns of limestone filler on the interfacial interaction performance of asphalt-filler interface. The results inferred that form factor and specific surface area were decisive factors for the asphalt-filler interfacial interaction. The observations highlighted the implication significance for the selecting suitable mineral fillers with superior asphalt cementing-filling systems.